Correlation of Biomarker Expression in Colonic Mucosa with Disease Phenotype in Crohn’s Disease and Ulcerative Colitis - Bruno, Maria E. C. (Dig Dis Sci, 2015)
BACKGROUND: Inflammatory bowel diseases (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), are characterized by chronic intestinal inflammation due to immunological, microbial and environmental factors in genetically predisposed individuals. Advances in the diagnosis, prognosis and treatment of IBD require the identification of robust biomarkers that can be used for molecular classification of diverse disease presentations. We previously identified five genes, RELA, TNFAIP3 (A20), PIGR, TNF and IL8, whose mRNA levels in colonic mucosal biopsies could be used in a multivariate analysis to classify patients with Crohn’s disease (CD) based on disease behavior and responses to therapy. AIM: We compared expression of these 5 biomarkers in IBD patients classified as having CD or ulcerative colitis (UC), and in healthy controls. RESULTS: Patients with CD were characterized as having decreased median expression of TNFAIP3, PIGR and TNF in non-inflamed colonic mucosa as compared to healthy controls. By contrast, UC patients exhibited decreased expression of PIGR and elevated expression of IL8 in colonic mucosa compared to healthy controls. A multivariate analysis combining mRNA levels for all 5 genes resulted in segregation of individuals based on disease presentation (CD vs. UC) as well as severity, i.e., patients in remission vs. those with acute colitis at the time of biopsy. CONCLUSION: We propose that this approach could be used as a model for molecular classification of IBD patients, which could further be enhanced by the inclusion of additional genes that are identified by functional studies, global gene expression analyses, and genome-wide association studies.